Effects of Adrenaline Infusion on Platelet Number, Volume and Release Reaction - Lande, K; Gjesdal, K; Fønstelien, E; Kjeldsen, S E; Eide, I (Thrombosis and Haemostasis, 1985)
At the end of a diagnostic right heart catheterization ten patients received an intravenous infusion of l-adrenaline which gradually increased the arterial plasma adrenaline concentration from resting physiological values to high values as seen during myocardial infarction, pheochromocytoma and hypoglycemia. Blood was sampled from the brachial artery, femoral vein and hepatic vein. During the adrenaline infusion venous beta-thromboglobulin concentrations increased 23% from 61 ± 5 to 80 ± 7 μg/l (mean ± SE), arterial platelet counts 20% from 212 ± 17 to 253 ± 25 × 109/l and arterial platelet volume 4% from 7.25 ± 0.20 to 7.56 ± 0.21 femtoliter. All changes were significant at the 5% level. Thus, acute increments of arterial plasma adrenaline significantly stimulated the blood platelet parameters studied.
Keywords: Beta-thromboglobulin; Catecholamines; Platelet function; Thrombosis